The contributions of community seed saving to health and wellbeing: A qualitative study in Thunder Bay, Canada - Rachel L.W. Portinga; Charles Z. Levkoe; Lindsay P. Galway (Wellbeing, Space and Society)
This paper positions community seed saving (CSS) as collective knowledge and practices used to cultivate, collect, conserve, exchange, and advocate for regionally adapted seeds as a foundation of healthy and sustainable food systems. Qualitative research involved twelve interviews with community seed savers in Thunder Bay, Canada. We explored the relationships to participants’ health and wellbeing through themes of physical health, mental, emotional, and spiritual health, and relationships and reciprocity. The findings illustrate that CSS can directly benefit individuals and influence social and ecological determinants of health. We argue that public health should consider CSS a health promotion intervention and an important future direction for research.